Dampak Inflasi terhadap Daya Beli Masyarakat di Lampung Tahun 2024 dalam Perspektif Ekonomi Makro - Annisa Istikomah; Cahyani Dwi Erawati; Rini Agustin Muda; Amanda Aulia; Suci Hayati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to understand the impact of inflation on the purchasing power of communities in Lampung Province throughout 2024 from a macroeconomic perspective using a qualitative approach. The persistent fluctuations in inflation over the year have triggered various responses and adaptation strategies among the public, particularly within economically vulnerable groups. Through in-depth interviews with various informants—such as small business owners, housewives, and informal sector workers—this study finds that inflation has influenced consumption patterns, spending priorities, and how people manage their daily income. A noticeable decline in purchasing power is observed in essential needs and healthcare services. Common coping strategies include switching to alternative products, taking on debt, or reducing overall consumption. The findings suggest that inflation has not only economic implications but also social consequences, highlighting the importance of social protection policies and price stabilization efforts to maintain household economic resiliencej.